Gingival overgrowth caused by vitamin C deficiency associated with metabolic syndrome and severe periodontal infection: a case report. Issue 6 (4th September 2014) - Omori, Kazuhiro; Hanayama, Yoshihisa; Naruishi, Koji; Akiyama, Kentaro; Maeda, Hiroshi; Otsuka, Fumio; Takashiba, Shogo
Abstract It has been suggested that vitamin C deficiency/scurvy is associated with gingival inflammatory changes; however, the disorder is very infrequently encountered in the modern era. Here, we report a case of extensive gingival overgrowth caused by vitamin C deficiency associated with metabolic syndrome and severe periodontal infection.